2002
DOI: 10.1038/modpathol.3880545
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time t(14;18)(q32;q21) PCR Assay Combined with High-Resolution Capillary Electrophoresis: A Novel and Rapid Approach that Allows Accurate Quantitation and Size Determination of bcl-2/JH Fusion Sequences

Abstract: Follicular lymphoma is characterized by the presence of the t(14;18)(q32;q21) chromosomal translocation that juxtaposes the bcl-2 gene at 18q21 with the immunoglobulin heavy chain (IgH) locus at 14q32. We have previously shown that accurate quantitation of t(14;18)-carrying cells in follicular lymphoma patients can be achieved by non-gelbased real-time TaqMan polymerase chain reaction (PCR; Applied Biosystems, Foster City, CA). Since our report, several studies have demonstrated that real-time PCR is highly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…[7][8][9] During the last few years, different quantitative PCR assays have been developed. [10][11][12] These methods provide a more reliable tool for an accurate evaluation of BCL2/ IgH ϩ cells in the BM or peripheral blood (PB) 13 and allow a better molecular monitoring of minimal residual disease after different therapeutic protocols. Moreover, some studies have provided evidence that real-time quantitative PCR (RQ-PCR) evaluation before and after autologous transplantation may predict the clinical course of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] During the last few years, different quantitative PCR assays have been developed. [10][11][12] These methods provide a more reliable tool for an accurate evaluation of BCL2/ IgH ϩ cells in the BM or peripheral blood (PB) 13 and allow a better molecular monitoring of minimal residual disease after different therapeutic protocols. Moreover, some studies have provided evidence that real-time quantitative PCR (RQ-PCR) evaluation before and after autologous transplantation may predict the clinical course of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that PCR products labeled during realtime PCR by incorporation of a fluorescent dye-labeled primer can be resolved by CE, allowing precise size determination of each bcl-2/JH fusion sequence. 15 This assay allowed us to recognize identically sized clones in sequential biopsy specimens from two patients. One patient (patient 19) had four sequential bone marrow samples in which we identified a clone of identical size, 108 bp, in each specimen during the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the amplified bcl-2/JH fusion sequences are labeled with a fluorescent dye, NED (Applied Biosystems), in this real-time PCR assay as we described previously. 15 The labeling of the amplification products allows rapid determination of the size of the bcl-2/JH fusion sequences following real-time PCR by capillary electrophoresis (CE). As amplicon size is helpful for excluding contamination and is also commonly used to demonstrate clonal identity between pre-and posttreatment specimens, multiplex real-time TaqMan PCR combined with CE provides a simple and rapid approach for monitoring minimal residual disease facilitating highthroughput analysis of multiple samples.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…174 (ii) t(14;18) PCR for MRD testing and monitoring Sensitive nested t(14;18) PCR assays with analytical sensitivities of 1 in 10 5 -10 6 cells are used for MRD detection and monitoring, and for assessing the efficacy of marrow purging prior to autologous transplantion. [177][178][179][180] Where available, RQ-PCR assays are now the preferred method of testing, using TaqMan and LightCycler systems, 166,[181][182][183][184][185] which are at least as sensitive as conventional nested assays. Their high analytical sensitivity mandates caution in interpreting 'molecular relapse' in treated patients, as translocation-positive cells in normal individuals can be detected at levels as high as 1 in 10 4 .…”
Section: Testing For Chromosomal Translocations By Pcr and Fishmentioning
confidence: 99%